2020
DOI: 10.1016/j.brs.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating high- and low-frequency neuro-cardiac-guided TMS for probing the frontal vagal pathway

Abstract: Background: Investigating approaches for determining a functionally meaningful dorsolateral prefrontal cortex (DLPFC) stimulation site is imperative for optimising repetitive transcranial magnetic stimulation (rTMS) response rates for treatment-resistant depression. One proposed approach is neuro-cardiacguided rTMS (NCG-TMS) in which high frequency rTMS is applied to the DLPFC to determine the site of greatest heart rate deceleration. This site is thought to index a frontal-vagal autonomic pathway that interse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…When the changes in heart rate of patients during TMS application are a clinical concern, then our results indicate that stimulation during diastole can prevent these unwanted changes. In contrast, synchronization of TMS with systolic activity might be relevant for treatment of clinical subgroups, such as depression, which is often associated with decreased heart rate variability and increased heart rate [32][33][34] . Our results, therefore, suggest that application of TMS during systole or diastole might be helpful to optimize clinical protocols, which should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…When the changes in heart rate of patients during TMS application are a clinical concern, then our results indicate that stimulation during diastole can prevent these unwanted changes. In contrast, synchronization of TMS with systolic activity might be relevant for treatment of clinical subgroups, such as depression, which is often associated with decreased heart rate variability and increased heart rate [32][33][34] . Our results, therefore, suggest that application of TMS during systole or diastole might be helpful to optimize clinical protocols, which should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…There was variability between subjects in their optimal stimulation location although the most common effects were seen at the F3/F4 for EEG sites. A second study has provided a partial replication of these findings and also indicated that there may be variations that are frequency and hemisphere specific [26]. To date, studies investigating this NCG-TMS approach have established differences in heart rate variability between EEG sites.…”
Section: How Do We Localize Treatment To the Dlpfc?mentioning
confidence: 80%
“…Some have suggested that the 1 Hz rTMS may be better tolerated than HF protocols, while also having a better safety profile. 74 76 Low frequency, 1 Hz rTMS can also be delivered on more affordable equipment than HF protocols, which could decrease costs and therefore potentially increase accessibility to rTMS. 73 …”
Section: Obstacles To the Current Care Delivery Model And Effectiveness Issuesmentioning
confidence: 99%
“…Several studies in human subjects have also reported that DLPFC stimulation reliably modulates HR compared to other neighboring cortical areas, such as the motor cortex, that had no such effect on cardiac activity. 75 , 81 , 82 As such, neuro-cardiac-guided TMS (NCG-TMS) could show promise to improve target selection and optimize treatment response.…”
Section: Obstacles To the Current Care Delivery Model And Effectiveness Issuesmentioning
confidence: 99%